Impact of physiotherapy on orofacial manifestations of juvenile idiopathic arthritis - Stratos Vassis; Cory M. Resnick; Mette Nørgaard; Kathleen M. Strawn; Helle Grove; Beatrice Noeldeke; Troels Herlin; Thomas Klit Pedersen; Peter Bangsgaard Stoustrup (Pediatric Rheumatology Online Journal, 2023)
Abstract Background Physiotherapy appears as a promising therapy option for patients with Juvenile Idiopathic Arthritis (JIA) [1, 2], but the effects of physiotherapy and jaw exercises on JIA-related orofacial symptoms remain unknown [3]. The aim of this proof-of-concept study was to assess the impact of orofacial physiotherapy and home-exercise programs in patients with JIA and temporomandibular joint (TMJ) involvement. Methods Twelve patients with JIA and TMJ involvement received a treatment of physiotherapy, complemented by prescribed home exercises spanning over eight weeks. Orofacial symptoms and dysfunction were monitored pre-treatment, during treatment, after treatment, and at a three-months follow-up. Results Orofacial pain frequency and intensity significantly decreased during the course of the treatment (p = 0.009 and p = 0.006), with further reductions observed at the three-month follow-up (p = 0.007 and p = 0.002). During treatment, the mandibular function improved significantly in terms of maximal mouth opening capacity, laterotrusion, and protrusion. Conclusions This proof-of-concept study shows favourable effects of physiotherapy and home excercises in the management of JIA-related orofacial symptoms and dysfunctions.